The arms race between beet necrotic yellow vein virus and host resistance in sugar beet - Liebe, Sebastian; Maiss, Edgar; Varrelmann, Mark (Frontiers in Plant Science, 2023)
The beet necrotic yellow vein virus (BNYVV) causes the rhizomania disease in sugar beet (Beta vulgaris), which is controlled since more than two decades by cultivars harboring the Rz1 resistance gene. The development of resistance-breaking strains has been favored by a high selection pressure on the soil borne virus population. Resistance-breaking is associated with mutations at amino acid positions 67-70 (tetrad) in the RNA3 encoded pathogenicity factor P25 and the presence of an additional RNA component (RNA5). However, natural BNYVV populations are highly diverse making investigations on the resistance-breaking mechanism rather difficult. Therefore, we applied a reverse genetic system for BNYVV (A type) to study Rz1 resistance-breaking by direct agroinoculation of sugar beet seedlings. The biotest allowed a clear discrimination between susceptible and Rz1 resistant plants already four weeks after infection, and resistance-breaking was independent of the sugar beet Rz1 genotype. A comprehensive screen of natural tetrads for resistance-breaking revealed several new mutations allowing BNYVV to overcome Rz1. The supplementation of an additional RNA5 encoding the pathogenicity factor P26 allowed virus accumulation in the Rz1 genotype independent of the P25 tetrad. This suggests the presence of two distinct resistance-breaking mechanisms allowing BNYVV to overcome Rz1. Finally, we showed that the resistance-breaking effect of the tetrad and the RNA5 is specific to Rz1 and has no effect on the stability of the second resistance gene Rz2. Consequently, double resistant cultivars (Rz1+Rz2) will provide effective control of Rz1 resistance-breaking strains. Our study highlights the flexibility of the viral genome allowing BNYVV to overcome host resistance, which underlines the need for a continuous search for alternative resistance genes.